Business Development Menggunakan Model Bisnis Canva - Sofyan Mufti Prasetiyo; Dimyati; Angga Syaf Putra; Abdul Aziz (CV. Multi Kreasi Media, 2023)
In developing a business, it is necessary to implement a business model known as the Business Model Canvas. In this business model, the company tells about the company's internal and external conditions. The company's business model canvas displays a block/business element model consisting of nine elements. This approach is used to apply the implementation of the Business Model Canvas in the UKM